Slow Moving Raw Material Layout Improvement Proposed Using Shared Storage Method In Production Planning And Inventory Control Department - Riyan Eko Budiyanto; Brav Deva Bernadhi; Novi Marlyana (Journal of Applied Science and Technology, 2023)
Layout is a decision that determines the efficiency of an operation in the long term. Many strategic impacts occur from the results of decisions about layout, including capacity, process, flexibility, cost, quality of work environment, customer contact and corporate image. An effective layout helps companies achieve a strategy that supports the business strategy that has been set between differentiation, low cost and fast response.At this time there are problems that arise in the material warehouse, namely when Warehouse employees will take materials for the purposes of the production process, the placement of materials in the warehouse is still irregular or still not neat in making the preparation of materials, so things like this cause time ineffectiveness in the process of taking materials in a warehouse. warehouse area and make it difficult for workers because there are no storage area instructions.The results of the Shared Storage approach can minimize the material handling distance, the total distance traveled in the initial layout is 2362.9 meters. The total mileage of the proposed layout is 1850.30 meters. There is a difference in the total mileage of 512.6 meters or 21.69% of the total initial mileage. This means that the proposed layout can shorten the distance traveled by warehouse employees in taking the materials needed in the delivery of the production process